THE ROLE OF TEACHING AND LEARNING IN THE DEVELOPMENT OF PUPILS PERSONALITY - Vasiliauskas, Romanas (Acta Paedagogica Vilnensia, 2009)
Learning as a complex process in which the child’s experience is determined not only by nature and ways of learning, but also by the condition and factors of the environment are analysed in this article. Among various authors who studied the relation between learning and the child’s development, J. Vaitkevičius is noted for efforts in analyzing didactic inseparably from other branches of science and in relating teaching and learning with child’s personality development. The author treats learning as an interaction of the teacher and pupils and among various factors he emphasizes three sides of learning – pedagogical, psychological and sociological and notes the necessity of their subordination. The author’s holistic views of teaching and learning, its structure, the importance of interactive learning in conveying the contents of education are revealed in the article. Recent teaching theories such as structuralism in which the significance of the process take place not only at school and also beyond as well as that of the context in the cognitive and emotional development of pupils are discussed in this study as well.
Keywords: didactics; learning process; structure of learning process; model of learning; interaction; development; personality